Summer Greengram Cultivation Demonstrates Efficient Energy Dynamics and Economic Viability - Jaidka, Manpreet; Kaur, Arshdeep; Brar, Amandeep Singh (International Journal of Bio-resource and Stress Management, 2025)
The frontline demonstrations of summer greengram were conducted in district Moga, Punjab, India during summer (March–June, 2017, 2019 and 2021) to evaluate the performance of recommended production technologies with farmers’ practices. The data collected was further subjected to analyse the block wise energy footprints of the summer greengram to study the ecological and economical variability. The results revealed that demonstration plots recorded significantly higher seed yield and better B:C in demonstration plots than FPP in all blocks. In 2017 and 2019, highest value of performance indicator such as extension gap was observed in block Moga I followed by Nihal Singh Wala and Moga II with lowest value in Baghapurana block. In 2021, highest value of extension gap was recorded in Moga II block followed by Moga I and Baghapurana. The technology gap was recorded less than one in all the blocks during 2017 and 2019 which indicates that demonstration plots realised higher seed yield than potential yield. In 2017, lowest technology index was recorded in Moga I block (-0.14) followed by Nihal Singh Wala (-0.13) and Baghapurana (-0.12). In 2021, minimum value was recorded in Nihal Singh Wala (-0.08) block. Over the years, demonstration plots registered significantly different energy footprints such as energy input, energy output, energy use efficiency, energy productivity, net energy and energy profitability than FPP. From the data, it can be concluded that cultivation of summer greengram in all the blocks of district Moga is economically as well as ecologically viable with highly efficient energy footprints.